2012
DOI: 10.1139/y11-118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atorvastatin and carboxymethylated glucan on the serum lipoprotein profile and MMP activity of mice with lipemia induced by poloxamer 407

Abstract: The effects of atorvastatin and carboxymethylated β-glucan (CMG) on the lipoprotein-cholesterol (LP-C) and lipoprotein-triglyceride (LP-TG) fractions and subfractions at the early stage of murine hyperlipidemia, and its pleiotropic anti-inflammatory effects, were studied. Atorvastatin and CMG were administered in ICR male mice with acute lipemia induced with a single injection of poloxamer 407 (P-407). A novel small-angle X-ray scattering method for the determination of fractional and subfractional composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Interestingly, the appearance of organelle-free zones and cytolysis of some hepatocytes occurred in the 1-month model, as shown in the EM study, but this was not observed after a single dose of P-407 (Korolenko et al ., 2012a). However, a common macrophage storage syndrome was observed in both models.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the appearance of organelle-free zones and cytolysis of some hepatocytes occurred in the 1-month model, as shown in the EM study, but this was not observed after a single dose of P-407 (Korolenko et al ., 2012a). However, a common macrophage storage syndrome was observed in both models.…”
Section: Discussionmentioning
confidence: 99%
“…The main finding in this study is that mannan C. albicans serotype A functioned as an effective stimulator of murine macrophages and exerted a hypolipidaemic effect in P‐407‐induced hyperlipidaemic mice following parenteral administration. Interestingly, we have previously shown that chemically modified (partially water‐soluble) yeast polysaccharides, such as carboxymethylated β‐glucan, also exerted a hypolipidaemic effect in the P‐407‐induced hyperlipidaemic mouse model . Thus, a brief summary of our current findings using mannan C. albicans serotype A will be presented.…”
Section: Discussionmentioning
confidence: 95%
“…To determine the effects of mannans in the non‐hyperlipidaemic state, a second group of mice received mannan A in the corresponding doses and manner of administration as described above, but no P‐407 to induce hyperlipidaemia. For comparative purposes, a third group of mice was administered atorvastatin (75 mg/kg) (Atoris; KRKA, Novo mesto, Slovenia) by oral gavage at 24 and 48 h before an injection of P‐407 . Control mice received an equivalent volume (0.5 ml) of saline only.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations